THE EFFECT OF THREE STEP INTERVIEW TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING ABILITY - Syaifudin Latif Darmawan; Aulia Hanifah Qomar; Nandita Rosalina (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Speaking is considered as an important skill to be accomplished by students. Speaking is related to the pronunciation of words that aim to convey what is to be conveyed both of feelings or ideas. However, there were some problems that make human could not express their ideas. They are such as difficult to pronounce the words, low vocabulary, and misunderstanding. The main purpose of this research is to know whether Three-Step Interview Technique effective towards students’ Speaking Ability at eleventh grade of MA Darul A’mal Metro. The population of the research was the students on the eleventh grade in MA Darul A’mal Metro. The sampling technique was random sampling technique. The researcherschose social and science class as the sampling. Based on the result of data analysis, the mean score of post-test in experimental class was13.26 and the mean score of post-test in control class was 12.00. It showed that the students’ post- test score in experimental class was higher than students’ post-test score in control class. The result can be seen from sig. (2-tailed) of the equal variance assumed in the independent sample test table which the sig. (2-tailed) is 0.043. It is lower than α = 0.05 and it means that Ho is rejected and Ha is accepted. It showed that there was significant influence of using three-step interview towards students’ speaking ability at the first semester of the eleventh grade of MA Darul A’mal. Speaking is considered as an important skill to be accomplished by students. Speaking is related to the pronunciation of words that aim to convey what is to be conveyed both of feelings or ideas. However, there were some problems that make human could not express their ideas. They are such as difficult to pronounce the words, low vocabulary, and misunderstanding. The main purpose of this research is to know whether Three-Step Interview Technique effective towards students’ Speaking Ability at eleventh grade of MA Darul A’mal Metro. The population of the research was the students on the eleventh grade in MA Darul A’mal Metro. The sampling technique was random sampling technique. The researcherschose social and science class as the sampling. Based on the result of data analysis, the mean score of post-test in experimental class was13.26 and the mean score of post-test in control class was 12.00. It showed that the students’ post- test score in experimental class was higher than students’ post-test score in control class. The result can be seen from sig. (2-tailed) of the equal variance assumed in the independent sample test table which the sig. (2-tailed) is 0.043. It is lower than α = 0.05 and it means that Ho is rejected and Ha is accepted. It showed that there was significant influence of using three-step interview towards students’ speaking ability at the first semester of the eleventh grade of MA Darul A’mal.